Gen Z Job Stress in High Regulated Work Environment Case From Bank Industry - Fauzi Djibran (Global Leadership Organizational Research in Management, 2025)
The increasing presence of Generation Z (Gen Z) in the banking industry presents unique challenges, especially in highly regulated work environments. Gen Z employees prioritize work-life balance, seek continuous personal and professional development, and expect a more flexible and transparent workplace culture. However, the stringent regulatory requirements in the banking sector impose high job demands, administrative burdens, and intense supervision, which may lead to significant job stress among young employees. This study aims to explore the experiences of Gen Z employees in coping with regulatory pressures in the banking industry and to identify their adaptation strategies to manage workplace stress. Using a qualitative approach, the research investigates how leadership styles, job autonomy, and financial well-being influence Gen Z's stress levels and job satisfaction. Findings indicate that supportive leadership, clear communication, and flexible work arrangements can mitigate stress and enhance employee retention. The study offers practical recommendations for financial institutions to implement employee-centred policies that align with Gen Z's expectations while maintaining compliance with industry regulations.